Genome-wide scan in Portuguese Island families identifies 5q31-5q35 as a susceptibility locus for schizophrenia and psychosis - Sklar, P. (2017)
Schizophrenia is a common psychiatric disorder with a complex genetic etiology. To understand the genetic basis of this syndrome in Portuguese Island populations, we performed a genome-wide scan of 29 families with schizophrenia, which identified a single region on 5q31-5q35 with strong linkage (NPL=3.09, P=0.0012 at D5S820). Empirical simulations set a genome-wide threshold of NPL=3.10 for significant linkage. Additional support for this locus in schizophrenia comes from higher-density mapping and mapping of 11 additional families. The combined set of 40 families had a peak NPL=3.28 (P=0.00066) at markers D5S2112-D5S820. These data and previous linkage findings from other investigators provide strong and consistent evidence for this genomic region as a susceptibility locus for schizophrenia. Exploratory analyses of a novel phenotype, psychosis, in families with schizophrenia and bipolar disorder detected evidence for linkage to the same markers as found in schizophrenia (peak NPL=3.03, P=0.0012 at D5S820), suggesting that this locus may be responsible for the psychotic symptoms observed in both diseases.